Chief financial officer profiles and financial performance among top 100 companies in telecommunication industry / Shafiqah Amirah Amirudin ... [et al.] - Amirudin, Shafiqah Amirah; Mat Yatim, Siti Nur Atiqah; Mohd Fadhillah, Zatty Ibtika; Abdul Rahim, Memiyanty (2021)
The telecommunication industry is one of the thriving markets in Malaysia. To date, there are 15 public listed telecommunication companies, including four (4) companies that are the largest network operators and major line providers in the country. These companies, Telekom Malaysia Berhad, Axiata Berhad, Digi.com Berhad, and Maxis Berhad, have near-monopoly position in the country. Telecommunications can be defined as the means of electronic transmission of information over a distance in the form of voice telephone calls, data, text, images, or video (Newton, 2000). It is an essential sector in the country as modernization requires advanced telecommunication systems to ensure the smooth running of databases and machinery. The relationship between the characteristics of the CFOs and the financial performance of the companies in the telecommunication industry will be analyzed in this paper. The telecommunication industry provides essential services as it helps connect people. According to Wilson (2020), people have been using telecommunication services such as internet data connection and telephone lines coverage extensively to facilitate their work in recent years. Next, Hoitash, Hoitash, and Kurt (2016), and Liu, Gan, and Karim (2021) defined a Chief Financial Officer (CFO) as the person responsible for supervising the company's financial and economic performance. Meanwhile, financial performance refers to how well the company is doing to achieve its targeted economic goals and be among the best in the industry after a certain period (Fatihudin, Jusni & Mochklas, 2018). Companies must have an excellent financial performance to increase investors' confidence in investing in their company.